Осмотично активні речовини в листках рослин-інтродуцентів роду Chaenomeles Lindl. - Zaitseva, I.O.; Dolgova, L.G. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The dynamic quantity of fractions of soluble sugars and proteins in leaves of species of genus Chaenomeles Lіndl. have been studied during vegetative periods. Dependence of their content on phases of seasonal development and hydrothermal factors in the introduction region is determined. The content of osmotic substances increased under the conditions of water and temperature stresses. The infinite complex of sugars and proteins plays protective function and increase resistance of introduced plants to draught and overheat in Steppe zone of Ukraine.